2004
DOI: 10.1182/blood-2003-06-2137
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL regulates normal erythroid maturation through an ERK-dependent pathway

Abstract: In order to investigate the biologic activity of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) on human erythropoiesis, glycophorin A (GPA) ؉ erythroid cells were generated in serum-free liquid phase from human cord blood (CB) CD34 ؉

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 34 publications
4
92
0
1
Order By: Relevance
“…Taxane-induced microtubule damage also triggers signaling cascades that involve Erk1/2 (30, 31). Erk1/2 acts both upstream and downstream of TRAIL-R; therefore, it is also possible that activation of Erk1/2 occurs as a downstream effect of up-regulation of the TRAIL-R (17,18). Although p53 is known to induce the death receptors, it is unlikely that this mechanism is operative here as p53 up-regulation of these receptors occurs at the transcriptional level (19), and our experiments showed that paclitaxel induced TRAIL-R via a posttranscriptional mechanism (because mRNA levels were not increased).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxane-induced microtubule damage also triggers signaling cascades that involve Erk1/2 (30, 31). Erk1/2 acts both upstream and downstream of TRAIL-R; therefore, it is also possible that activation of Erk1/2 occurs as a downstream effect of up-regulation of the TRAIL-R (17,18). Although p53 is known to induce the death receptors, it is unlikely that this mechanism is operative here as p53 up-regulation of these receptors occurs at the transcriptional level (19), and our experiments showed that paclitaxel induced TRAIL-R via a posttranscriptional mechanism (because mRNA levels were not increased).…”
Section: Discussionmentioning
confidence: 99%
“…11). Erk1/2 acts both upstream and downstream of TRAIL-R (17,18). In addition, it has been reported that TRAIL-R2 is a DNA damage -inducible, p53-regulated death receptor gene (19).…”
Section: Paclitaxel Enhances Tumor Uptake Of 99m Tc-ecl Abeled Trail-mentioning
confidence: 99%
“…Developing erythroid cells express CD95 and TRAIL receptors (5,36). To investigate whether IFN-␥ may inhibit erythropoiesis through different effectors, we analyzed the expression of members of the TNF/TNFR family, including TRAIL and the recently characterized proteins TWEAK and TL1A, in IFN-␥-treated erythroid precursor cells.…”
Section: Ifn-␥ Up-regulates Multiple Tnf Family Members On Immature Ementioning
confidence: 99%
“…[2][3][4] The ligand and its receptors are expressed at low levels in human hematopoietic progenitors under steady-state conditions; therefore, these cells are largely unaffected by this signaling pathway. [17][18][19] Among the known five TRAIL receptors, DR4 (TRAIL-R1) and DR5 (TRAIL-R2) are associated with transduction of apoptotic signals in humans, 16 whereas mice express only TRAIL-R2. 20,21 Although mRNA encoding TRAIL receptors DR4 and DR5 is frequently detected in CD34 þ progenitors, these cells were insensitive to apoptosis 22,23 even in the presence of low doses of doxorubicin.…”
Section: Introductionmentioning
confidence: 99%
“…23,28,29 Therefore, TRAIL may serve as a negative regulator of expanding clones in the distal stages of differentiation of all hematopoietic lineages. 13,[17][18][19]30,31 As umbilical cord blood (UCB) becomes an important source of hematopoietic progenitors for transplantation, we evaluated the effect of TRAIL in proximal stages of their activity. We recently showed that the Fas/Fas-ligand interaction transduces trophic signals in early stages of hematopoietic cell engraftment, 32 because the most primitive progenitors are insensitive to Fas-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%